2021
DOI: 10.3389/fped.2020.628072
|View full text |Cite
|
Sign up to set email alerts
|

Development of Psychological Problems Among Adolescents During School Closures Because of the COVID-19 Lockdown Phase in Italy: A Cross-Sectional Survey

Abstract: Background: Previous studies have shown that during COVID-19 pandemic, mainly due to the imposed lockdown, significant psychological problems had emerged in a significant part of the population, including older children and adolescents. School closure, leading to significant social isolation, was considered one of the most important reasons for pediatric mental health problems. However, how knowledge of COVID-19 related problems, modification of lifestyle and age, gender and severity of COVID-19 pandemic had i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
85
3
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 21 publications
6
85
3
4
Order By: Relevance
“…Most notably, when we took the participants' pre-pandemic mental health into account, we found a decrease in psychiatric symptoms among the adolescents who had more severe emotional and behavioral problems prior to the pandemic. These findings support different conclusions than most previous studies regarding the effects of the COVID-19 pandemic on mental health, which described an increase in mental health problems among adolescents [9][10][11][12] . Importantly, the majority of participating adolescents in our study reported symptoms in the normal range at both time points during the pandemic.…”
Section: Discussioncontrasting
confidence: 77%
“…Most notably, when we took the participants' pre-pandemic mental health into account, we found a decrease in psychiatric symptoms among the adolescents who had more severe emotional and behavioral problems prior to the pandemic. These findings support different conclusions than most previous studies regarding the effects of the COVID-19 pandemic on mental health, which described an increase in mental health problems among adolescents [9][10][11][12] . Importantly, the majority of participating adolescents in our study reported symptoms in the normal range at both time points during the pandemic.…”
Section: Discussioncontrasting
confidence: 77%
“…In addition, the closure of private and public schools, parks, and recreation centers resulted in changes in the overall mood of Brazilian adolescents, and sadness, irritability, and sleep problems have become quite usual. Impaired emotional status during the COVID19 pandemic has been previously shown by several studies and has been attributed to a disruption in education, physical activities, and socialization [45,46].…”
Section: Discussionmentioning
confidence: 74%
“…In addition to the assessment of psychological impact, some studies also evaluated the children's knowledge about COVID-19, their source of information, and their compliance to the measures dictated to prevent the spread of COVID-19. [36][37][38][39] While a large majority were seen to be following at least some social distancing, most of them were not able to follow all the measures outlined to prevent the spread. A sense of social responsibility was seen to be associated with a higher prevalence of following the hygiene and sanitization measures as well as social distancing.…”
Section: Discussionmentioning
confidence: 99%